A molecular characterization of inflammation in the bicipital tunnel. Issue 3 (8th January 2021) - Campbell, Abigail; Taylor, Samuel A.; O'Dea, Evan; Shorey, Mary; Warren, Russell F.; O'Brien, Stephen J.
Abstract : The pathophysiology of extra‐articular biceps disease is not fully understood. The purpose of the study was to assess molecular evidence of inflammation, degradation, and nociception within the 3 separate anatomic zones of the extra‐articular biceps tendon and its confining tunnel. Arthroscopic biopsies were taken from the bicipital tunnel from 11 patients with suspected biceps‐labrum complex disease undergoing subdeltoid biceps transfer to the conjoint tendon. Tissue was analyzed for mRNA expression of various inflammatory mediators including interleukin‐6, interleukin‐1β, transforming growth factor‐β (TGF‐β), matrix metalloproteinase‐13, and substance P precursor. Extra‐articular tissue was compared with intra‐articular tendon (internal control) to determine fold change in expression. Compared to intra‐articular tendon, extra‐articular biceps tendon and synovium have increased levels of these aforementioned mediators, significantly TGF‐β ( P = .012). In patients with clinical history of long head of the biceps tendon tendinopathy as well as arthroscopic findings of synovitis, tear, and loose bodies, pro‐inflammatory and degenerative cytokines were upregulated in the extra‐articular tendon. Inflammatory cytokines, degenerative mediators, and pain molecules associated with nociception were found within both the extra‐articular long head of biceps tendon and its constraining fibro‐osseous bicipital tunnel in patients with clinically evident biceps‐labral complex disease.